Application of two-dimensional optical spectroscopy: from ultrafast spectral diffusion to Lewis basicity - Do, Thanh Nhut (2020)
Two-dimensional optical spectroscopy (2DOS) is the optical version of the well-established 2D-NMR technique, e.g., COSY. With time resolution in the femtosecond regime, 2DOS is widely used to resolve the ultrafast frequency modulation dynamics, such as spectral diffusion, in various vibrational [1-2] and electronic [3-4] systems. Chlorophylls (Chls) a and b are two main types of photosynthetic pigments responsible for the light-harvesting and energy regulation of green plants on Earth. Here, we employ 2DOS to track the time evolution of the 2D peakshape (Fig. 1) and resolve the ultrafast spectral diffusion dynamics of the Chl Qy transition in various organic solvents. The obtained results suggest that Chls exhibit three different relaxation dynamics with the timescales of sub-picosecond (sub-ps), several ps and tens to hundreds of ps.